Patterns and Determinants of Primary Tooth Extraction in Children: A Study in an Indian Tertiary Care Dental Setting - Shamsher Singh; Vikram Singh; Swati Sharma; Chirag Patel; Ajoy Kumar Shahi; Vanisha Mehta; Pranav V Manek (Wolters Kluwer Medknow Publications, 2024)
Introduction: Preservation of primary teeth is essential for optimal oral health in children; however, there is limited research on primary tooth extraction patterns in India. This study aimed to investigate the reasons for and patterns of primary tooth extraction in children in an Indian tertiary care dental setting. Methodology: This retrospective cross-sectional study analyzed dental records of children aged up to 14 years who underwent tooth extraction under local anesthesia from January to December 2023. Demographic data, reasons for extraction, and tooth types extracted were collected and analyzed using descriptive statistics and the Chi-square test. Results: Among the 261 subjects studied, there were 132 males and 129 females. Dental caries was the leading cause of extraction (42.6%), followed by mobility (20.8%) and over-retention (17.3%). Maxillary teeth were extracted more frequently than mandibular teeth, with central incisors being the most commonly extracted. Conclusion: This study highlights the prevalence of dental caries as the primary reason for primary tooth extraction in Indian children. Gender-specific differences were observed in extraction reasons, and maxillary teeth were more frequently extracted than mandibular teeth. These findings emphasize the importance of targeted preventive strategies to address dental caries and promote optimal oral health in children in India.